1992
DOI: 10.1093/nar/20.20.5365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chimeric mRNAs derived from theSTE3mRNA identifies multiple regions within yeast mRNAs that modulate mRNA decay

Abstract: In the yeast Saccharomyces cerevisiae unstable mRNAs decay 10-20 fold more rapidly than stable mRNAs. In order to examine the basis for the differences in decay rate of the unstable STE3 mRNA and the stable PGK1 and ACT1 mRNAs we have constructed and measured the decay rates of numerous chimeric mRNAs. These experiments indicate that multiple regions within yeast mRNAs are involved in modulating mRNA decay rates. Our results suggest that at least two regions within the STE3 mRNA are involved in stimulating rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 26 publications
7
52
1
Order By: Relevance
“…Our data are in contrast to those of a previous report which concluded that the replacement of the first 164 codons of the PGKI mRNA with all rare codons was sufficient to destabilize this transcript (20). However, since these codon changes made numerous alterations in the primary sequence of the PGKI coding sequence within a region that has been implicated in transcriptional activation (24) and/or mRNA stability (16) and no measurements of mRNA decay rate or transcription rate were performed, this prior conclusion must be treated with extreme caution.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our data are in contrast to those of a previous report which concluded that the replacement of the first 164 codons of the PGKI mRNA with all rare codons was sufficient to destabilize this transcript (20). However, since these codon changes made numerous alterations in the primary sequence of the PGKI coding sequence within a region that has been implicated in transcriptional activation (24) and/or mRNA stability (16) and no measurements of mRNA decay rate or transcription rate were performed, this prior conclusion must be treated with extreme caution.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results defining the MIE are consistent with the general view that specific sequences within mRNAs control their halflives (9). However, several of our results reported here and elsewhere (16,25) suggest that the observed decay rates of different mRNAs may depend on the combined effects of multiple elements within each mRNA. For example, although the MIE can increase the rate of decay of the PGKI transcript by fivefold, this chimeric transcript is still approximately two-to threefold more stable than the parental MATod mRNA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations